Aortic valve morphology and paravalvular leak regression after a self-expandable transcatheter aortic valve replacement - Jin, Qinchun; Li, Wei; Chen, Shasha; Li, Mingfei; Zhou, Daxin; Zhang, Xiaochun; Ge, Junbo (Frontiers in Physiology, 2023)
Aims: To compare paravalvular leak (PVL) changes after transcatheter aortic valve replacement (TAVR) with self-expandable prosthesis between different aortic valve morphologies and evaluate the impact of PVL regression on clinical prognosis. Methods: Patients with aortic stenosis (AS) successfully treated with self-expandable TAVR who were followed up for at least 1 year at our centre were consecutively enrolled from Jan 2016 to August 2019. Paired serial changes in PVL and other haemodynamic parameters by echocardiography were collected and compared between the bicuspid valve (BAV) and tricuspid aortic valve (TAV). A logistic regression model was used to explore the predictors of PVL regression (≥1 grade) at 1 year after TAVR, while its impacts on subsequent clinical outcomes (all-cause mortality and rehospitalization for heart failure (HFH)) were further evaluated using Kaplan‒Meier analysis. Results: A total of 153 BAV and 114 TAV patients were finally enrolled; haemodynamic parameters and PVL severity were comparable before discharge between the two groups. Peak transaortic velocity, mean transvalvular gradient and effective orifice area all significantly improved (p＜0.05) without intergroup differences at all follow-up time points. Significant PVL reduction was observed only in TAV (1.75% vs. 4.39%, p=0.029), while moderate PVL was more prevalent in BAV (7.19% vs. 1.75%, p = 0.041) at the 1-year follow-up. Multivariable analyses identified BAV, asymmetric calcification and undersizing as independent predictors of failure of 1-year PVL reduction in patients with mild or moderate PVL after discharge. Patients without PVL reduction within 1 year showed relatively higher 2-year all-cause mortality and HFH (HR: 5.994, 95% CI: 1.691-21.240), p=0.053) rates thereafter. Conclusion: In AS patients after self-expandable TAVR, PVL regression within 1 year was less prevalent in BAV morphology. Failure of PVL reduction might lead to an increased risk of poorer prognosis in the long run.